PEMBERIAN ASI EKSKLUSIF DAN MAKANAN PENDAMPING ASI BERHUBUNGAN DENGAN STATUS GIZI BALITA USIA 12 - 24 BULAN - Erika Yulita Ichwan; Rosni Lubis; Ayi Diah Damayani (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Malnutrition is still a public health problem and can be the cause of death, especially inhigh risk groups (infants and toddlers). One of the main factors that contributes to malnutritionis the inappropriate practices of breastfeeding and complementary feeding.This was ananalytical research using a survey method of cross sectional . The Sample used 75 respondents,mothers of toddlers with 12- 24 months of age in the area of Puskesmas Cipinang BesarUtara in November 2014. Using a questionnaire, the data were analyzed using chi-squarewith ? = 0.05.The Result of study showed that majority respondents, namely 66 people (88%) were found at the group age of 20 - 34 months. Moreover, respondents with educationperiod of ? 9 years were 52 people (69 %) , having 3-4 children were 40 people (53 %) ,had income per month ?Rp.2.441.301 were 60 people (80 %) and unemployed mothers were58 people (77 %). Toddlers with good nutritional status were 46 (61 %) , exclusivebreastfeeding were 36 people (48 %), age of the complementary feeding < 6 months and>7 months were 41 people (57 %), factory - made complementary foods were 38 people(50 %). Factors related with the nutritional status of toddlers were exclusive breastfeedingp-value = 0,000 (<0,000), and the age of complementary feeding p-value = 0,000 (<0,000).Based on the result, it is suggested that the nursing mothers, local cadres of integratedhealth office (called as Kader Posyandu), and midwives pay more attention to the factorsaffected the nutritional status of toddlers to determine good attitudes and appropriateinterventions to increase the nutritional status of toddlers.